A complete analysis on PHA production and their rates usingsunflower oil and mixed cultures : hydraulic retention times (HRT) effects - Yunus, S.; Ujang, Zaini; M. R., Salim; Ahmad, A.; Marpongahtun, Marpongahtun (Fakultas Matematika dan Ilmu Pengetahuan Alam AUSU, Indonesia, 2005)
Abilities of four HRT/SRT experiments were conducted to assess the optimal conditions for PHA production using commercial fatty acid; sunflower oil (SO). Since the systems were conducted in a fast regime (uptake rate), no idle or settling phase is adapted resulting HRT ≈ SRT (HRT/SRT). First, the effect of carbon source was investigated. The system was dependent on microbial activity and operating conditions, particularly HRT/SRT, COD/N, growth and accumulation conditions. The target was to maintan the bacterial growth, so the capability of storage polymer (polyhydroxyalkanoates, PHAs) will significant in the survival period (limiting condition of nutrient). The PHA constituents such as HV and HH were also examined in order to compare the polyester production in commercial oil compositions. The typical composition of SO mainly contains long-chain-fatty-acid (LCFA) under unsaturated fatty acid (C14:1 – C18:3) and therefore, the bacterial not much utilize it. Here also, the highest PHA productions can reach up to 33.77% of dry weight because the capability of storage mechanisms. Substrate uptake rates were found not to be proportional to the cell growth, suggesting that only a small fraction of the cell biomass was responsible for the main part of the substrate uptake. Based on these experiments, new fabrication of experiment will usefulness for the development of renewable carbon sources (especially from oil manufacturing) and sufficient for PHA production.